DEVELOPMENT OF UKRAINIAN FARMS ON THE BASIS OF INSTITUTIONAL TRANSFORMATION - Zhmur, Nataliia; Malykhina, Alina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to study the development of farms in Ukraine on the basis of institutional transformation, as well as analysis of regulatory and legal regulation of farms. Research methods: the research was conducted with the use of generally accepted methods of scientific knowledge, such as: comparative law, system structural, method of analysis of current domestic legislation. Results: the stage-by-stage development of farms was studied, normative-legal acts on the development and activity of farms were analyzed. Discussion: the peculiarities of the farm, is an important objective factor that necessitates special regulation of their activities in agricultural law. Uncertainty of the state policy and the activities of regulatory bodies to address legislative and organizational problems of farming development has a negative impact on the competitiveness of farms. The competitiveness of farms is a consequence of the interests of their owners in the general system of public support for their activities, public policy aimed at ensuring transparent relations in product markets and factors of production, promoting entrepreneurial activity of Ukrainian peasants. Farms are an important component of agricultural policy in Ukraine’s economy. They ensure the efficient use of agricultural resources, as the economic interest of the producers themselves, who are mainly the owners of resources or tenants, is fully realized. Therefore, state support in business is a very important component of accessibility and success in this area. During the period of institutional transformations of farms, they became an integral part of the agricultural sector of Ukraine’s economy, a source of maintaining food security and providing high-quality products, a common form of self-realization of the peasant as an entrepreneur and individual. In connection with Ukraine’s intentions to integrate into the European market space, creating an environment for the development of the competitiveness of farms is a necessary precondition for the socio-economic development of the Ukrainian countryside. The advantages of farming are: heredity of this type of agricultural business; economic care for the land and direct contact of the farmer with the rural community; the existence of one or more farms in the community provides an opportunity to increase the level of employment of the rural population; to solve socio-economic problems. Thus, farms are an important component of Ukraine’s agricultural policy. They ensure the efficient use of agricultural resources, as fully realized the economic interest of producers themselves, who are mainly the owners of resources or tenants.